Membangun Kepercayaan Diri Anak Menggunakan Metode CAMB (Cerita, Apresiasi, Motivasi, dan Biasakan) di Lembaga Swadaya Masyarakat Komunitas Peduli Anak (LSM KOPA) - Sarah Shahiba; Bengkel Ginting (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Confidence is a belief in yourself so that you are able to deal with various situations, usually self-confidence has a lot to do with one's relationships with other people. Each individual has a different level of self-confidence, it is influenced by several factors. It's not uncommon for someone to have doubts about their own abilities so they can't express themselves well. In an effort to increase children's confidence in KOPA NGOs by providing assistance through a mini project in the implementation of PKL II, using the groupwork method at the mezzo intervention level through the general intervention stage consisting of Engagement, Intake, Contract; Assessment; Planning/Planning; Intervention; Evaluation; and Termination. This groupwork consists of five children who are still in elementary school. The focus in solving clients' problems is the application of the CAMB (Story, Appreciation, Motivation, Get used to) method to assist clients in building their self-confidence. The aim of this program was stated to be achieved, this can be seen by increasing the confidence of the clients after getting help.